An evaluation of the differences in paediatric skeletal trauma between fatal simple short falls and physical abuse blunt impact loads: An international multicentre pilot study. (June 2021) - Rowbotham, Samantha K.; Blumenthal, Ryan; Delabarde, Tania; Legrand, Laurence; van der Walt, Elizabeth; Sutherland, Tom; Lockhat, Zarina; Arthurs, Owen J.
Highlights: Of forensic paediatric deaths, short falls comprised 0.1% and physical abuse 0.6%. Pilot findings suggest possible differences between short falls and physical abuse. Simple short falls resulted in simple linear neurocranial fractures. Physical abuse resulted in linear or complex skull fractures and postcranial trauma. Pilot data forms the foundation of the Registry of Paediatric Fatal Fractures (RPFF). Abstract: In cases where a deceased child exhibits trauma as a result of a physical abuse blunt impact load, a parent/caregiver may provide a simple short fall (SSF) as the justification for that trauma. The skeletal fractures remain difficult to differentiate between a SSF and physical abuse however, as both are the result of a blunt impact load, and are therefore biomechanically alike, and the rare nature of these fatalities means only anecdotal research has been available to validate such claims. The aim of this pilot study was to investigate if there may be differences in the skeletal fracture patterns and types resulting from SSFs compared with those resulting from physical abuse blunt impacts. Paediatric (<10 years) cases of fatal SSFs (≤1.5 m) and physical abuse were collected from the Victorian Institute of Forensic Medicine (Australia), Institut Médico-Légal de Paris (France), University of Pretoria (South Africa) and Great Ormond Street Hospital (England). For each case the intrinsic and extrinsic variables were recorded from medico-legal reports and skeletal trauma was documented using post-mortem computed tomography scans and/or skeletal surveys. Three SSFs and 18 physical abuse cases were identified. Of the SSF cases, two exhibited fractures; both of which were simple linear neurocranial fractures. Comparatively, 12 of the physical abuse cases exhibited fractures and these were distributed across the skeleton; 58% located only in the skull, 17% only in the post-cranial and 25% located in both. Skull fracture types were single linear, multiple linear and comminuted. This pilot study suggests, anecdotally, there may be differences in the fracture patterns and types between blunt impact loads resulting from a SSF and physical abuse. This data will form the foundation of the Registry of Paediatric Fatal Fractures (RPFF) which, with further multicentre contributions, would allow this finding to be validated.